Hubungan antara Frekuensi Konsumsi Junk Food dan Status Gizi dengan Kejadian Dysmenorrhea pada Siswi Sekolah Menengah Pertama IT Ar-Rayyan Surabaya - Rafita Fauziah; Lailatul Muniroh; Emyr Reisha Isaura (Universitas Airlangga, 2023)
Background: These days a lot of girls had menstrual problem. One of menstrual problems is painful menstruation, also known as dysmenorrhea. Dysmenorrhea is caused by eating junk food regularly and high fat content in junk food can promote increasing prostaglandins hormones. Other than that, abnormal body mass index impacts the hormonal imbalances. Objectives: This study aims to analyze the correlation between frequency of junk food consumption, and nutritional status with dysmenorrhea among students of Ar-Rayyan Surabaya Junior High School. Methods: This study is cross sectional study with sample of female students who experienced menstruation as much as 35 female students that were selected by simple random sampling. Nutritional status were measured using anthropometric measurement, and frequency consumption junk food were measured using SQ-FFQ (Semi Quantitative Food Frequency Questionnaire), and dysmenorrhea status were measured using likert scale questionnaire (never – always). In this study, data analysis used Spearman correlation test. Results: The results showed that 57.1% female students consumed junk food frequently and 51.4% of female students had fat in junk food intake â‰¥ 48.7 g, and 54.3% female students had normal nutritional status. There was no correlation between frequency of junk food consumption (p=0.099), and nutritional status (p=0.949) with dysmenorrhea among students of Ar-Rayyan Surabaya Junior High School. Conclusions: The conclusion of this study are there is no correlation between frequency of junk food consumption and nutritional status with incidence of dysmenorrhea. Therefore, high or low intake fats junk food, and normal or abnormal nutrition status can experience painful menstrual periods (dysmenorrhea). It is recommended for students to limit their intake of junk food, achieve and maintain a normal weight.